Monoamine Oxidase A Inhibits Lung Adenocarcinoma Cell Proliferation by Abrogating Aerobic Glycolysis - Huang, Yumin; Zhao, Wei; Ouyang, Xiaoping; Wu, Feng; Tao, Yujian; Shi, Minhua (Frontiers in Oncology, 2021)
Lung adenocarcinoma (LUAD) accounts for 30% of all lung cancers and is one of the causes of cancer-related death worldwide. As the role of monoamine oxidase A (MAOA) in LUAD remains unclear, in this study, we examine how MAOA affects LUAD cell proliferation. Analyses of both public data and our data reveal that the expression of MAOA is downregulated in LUAD compared with non-tumor tissue. In addition, the expression of MAOA in tumors correlates with clinicopathologic features, and the expression of MAOA serves as an independent biomarker in LUAD. In addition, the overexpression of MAOA inhibits LUAD cell proliferation by inducing G1 arrest in vitro. Further mechanistic studies show that MAOA abrogates aerobic glycolysis in LUAD cells by decreasing hexokinase 2 (HK2). Finally, the expression of HK2 shows a negative correlation with MAOA in LUAD, and high HK2 predicts poor clinical outcome. In conclusion, our findings indicate that MAOA functions as a tumor suppressor in LUAD. Our results indicate that the MAOA/HK2 axis could be potential targets in LUAD therapy.